The search for Baptist saints - Rees, Frank D. 1950- (2017)
This article reports on a project of the Commission on Baptist Doctrine and Christian Unity, within the Baptist World Alliance, to identify Baptist saints. The project seeks to apply the methodology proposed by James McClendon's Biography as Theology. The article situates the search for Baptist saints within the growing interest of Baptist scholars in a 'Baptist catholicity', specifically relating it to the priesthood of all the faithful. The methodology drawn from McClendon's work is outlined in some detail, focusing the study upon the convictions which give character to particular lives. Brief summaries are then presented of papers already received, offering examples from Germany, India, Jamaica and then a more detailed example from Australia. This example seeks also to demonstrate both the methodology and its application to a particular instance, Rev. Ron Ham, an Australian Baptist pastor. The article proposes that his life was shaped by the conviction that we live in God's world with God's people, and draws implications from this study for Baptist doctrine and for Christian unity.
Keywords: Baptist ecclesiology; James McClendon; biography as theology; Communion of saints; Discipleship; Saints